1991
DOI: 10.1037/0096-1523.17.1.232
|View full text |Cite
|
Sign up to set email alerts
|

Apparent size as a function of vertical gaze direction: New tests of an old hypothesis.

Abstract: The hypothesis was tested that the decline of apparent size with elevated gaze results from a latent tendency of the eyes to diverge and thus increased vergence effort. Through the use of a method of category estimation, the decline of apparent size on elevation or depression of gaze was found not to be different between subjects with larger or smaller changes of dark vergence and thus vergence effort. In a 2nd experiment, vergence effort was varied by varying gaze elevation and the angle of convergence. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This is known as the “angle of regard hypothesis.” In the present experiment, just such a visual angle was required for participants to see the tops of the targets while lying prone on the floor. However, there is no clear empirical evidence to support such a claim (e.g., Heuer, Wischmeyer, Brüwer, & Römer, 1991; Plug & Ross, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This is known as the “angle of regard hypothesis.” In the present experiment, just such a visual angle was required for participants to see the tops of the targets while lying prone on the floor. However, there is no clear empirical evidence to support such a claim (e.g., Heuer, Wischmeyer, Brüwer, & Römer, 1991; Plug & Ross, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This apparatus, however, was not necessarily perfect. For one thing, to view the artificial (virtual) moon superimposed on the half‐silvered mirror (5 cm × 5 cm), their participants must have been very restricted (see also Footnote 7). Even very small movements of the eye, head or body would have slipped the artificial moon away from the mirror, so it was necessary for the participant to fixate on the image of the moon without any eye‐head‐body movements.…”
mentioning
confidence: 99%
“… Vergence effort (muscular tension in the two coordinated eyes) has often been thought to be responsible for the effect of eye elevation on apparent size: more than 100 years ago, Zoth (1899) had taken vergence effort as a probable cause for the moon illusion. However, Heuer, Wischmeyer, Brüwer, and Römer (1991) showed that the difference in apparent size might not result from vergence effort, but dependent partly on vergence itself. …”
mentioning
confidence: 99%
“…von Hofsten, 1976). Alteration of vergence-specified distance may be achieved by introducing a bias to the vergence system (changing the open loop vergence bias, or heterophoria ) either by adapting to the presence of a prism over one eye (Owens & Leibowitz, 1980) or by fixating a close target for an extended period (Heuer, Wischmeyer, Bruwer, & Romer, 1991; Shebilske, Karmiohl, & Proffitt, 1983). It has been observed that inducing convergent biases results in the expected overestimation of distance (Ebenholtz & Wolfson, 1975; Heuer et al, 1991; Owens & Leibowitz, 1980; Shebilske et al, 1983).…”
mentioning
confidence: 99%
“…Alteration of vergence-specified distance may be achieved by introducing a bias to the vergence system (changing the open loop vergence bias, or heterophoria ) either by adapting to the presence of a prism over one eye (Owens & Leibowitz, 1980) or by fixating a close target for an extended period (Heuer, Wischmeyer, Bruwer, & Romer, 1991; Shebilske, Karmiohl, & Proffitt, 1983). It has been observed that inducing convergent biases results in the expected overestimation of distance (Ebenholtz & Wolfson, 1975; Heuer et al, 1991; Owens & Leibowitz, 1980; Shebilske et al, 1983). There are also several reports of distance underestimation following prolonged fixation of more distant stimuli, and these results have been attributed to the induction of divergent bias (Ebenholtz & Wolfson, 1975; Heuer & Luschow, 1983; Paap & Ebenholtz, 1976).…”
mentioning
confidence: 99%